The effects of solutions of maca (Lepidium meyenii) powder as a food/feed supplement on the viability of murine macrophage cells by digital image analysis - OMURTAG KORKMAZ, BURCU İREM (My University, 2021)
Maca (Lepidium meyenii) is a tuber root plant and belong to Brassicaceae family and recently used as a supplement in human and animal nutrition. In this study, it was aimed to investigate the cytotoxicity of two solutions (aqueous and ethanol) of maca root powder by digital image analysis. Maca powder was mixed in ultra distilled water and ethanol (1:2 w/v) for 24 h at 4 °C. The mixtures were centrifuged and the supernatants were ten-fold diluted for cytotoxic analysis of Raw 264.7 murine macrophage cells. After seeded the cell cultures in microplates, ten-fold dilutions (from 10-1 to 10-7 ) of both maca solutions were added as six replicates for 24 h. While the aqueous maca solution increased the number of dead cells at 10-1 (50 mg mL-1 ), the ethanolic solution statistically increased the number of dead cells at 10-1 , 10-2 and 10-3 (50, 5 and 0.5 mg mL-1 ) (P<0.01). In conclusion, the alcoholic preparation of maca powder caused a higher cytotoxic effect on the murine macrophage cells than the aqueous preparation due to the solvents and the dilution factor in this study.
Keywords: Lepidium meyenii; Food/Feed Supplement; Cytotoxicity